2013
DOI: 10.4323/rjlm.2013.185
|View full text |Cite
|
Sign up to set email alerts
|

Death caused by hemolytic-uremic syndrome. Case series

Abstract: Hemolytic-uremic syndrome is defined by a combination between renal failure, microangiopathic hemolytic anemia and thrombocytopenia; it usually appears in young children, is preceded by gastrointestinal enteritis and may involve other organs as well. The purpose of this article is to present a series of four cases of lethal hemolytic uremic syndrome and discuss its legal medicine consequences. For the first three cases an autopsy was not performed and the direct cause of death was considered brain involvement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, clinical use is limited by the ototoxic potential and the nephrotoxic effects of this drug. Nephrotoxicity was linked to the selective accumulation of gentamicin in the renal cortex [9], especially in proximal renal tubule (50 to 100 times higher concentration compared to the serum) and free radical production [3]. Studies in recent decades have shown that GM-induced nephrotoxicity is characterized by tubular necrosis, especially in the proximal tube.…”
Section: Animal Models and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clinical use is limited by the ototoxic potential and the nephrotoxic effects of this drug. Nephrotoxicity was linked to the selective accumulation of gentamicin in the renal cortex [9], especially in proximal renal tubule (50 to 100 times higher concentration compared to the serum) and free radical production [3]. Studies in recent decades have shown that GM-induced nephrotoxicity is characterized by tubular necrosis, especially in the proximal tube.…”
Section: Animal Models and Experimental Designmentioning
confidence: 99%
“…Regarding the main causes of renal failure it is well known and proved that type 1 and type 2 diabetes, arterial hypertension, arterial hypotension and the toxicity of certain substances play a major role in the development of renal lesions, leading to glomerular and intestitial damage [1][2][3]. Other studies describe that disturbances in lipidic metabolism (hypercholesterolemia), due to a cholesterolrich diet, can also worsen the renal dysfunction [4,5].…”
mentioning
confidence: 99%
“…The samples were sent to the Baylor College of Medicine Pathology and Histology Core, sectioned (~8 μm), mounted, and two slides x 3 sections were stained with H&E. Two images were taken per animal from the upper right and lower left quadrants of the tissue on a Nikon Eclipse 80i upright microscope using the 4x objective. Representative samples are shown based on blinded image analysis and histological labeling was included as similarly described [21][22][23][24] .…”
Section: Figure 1bandc)mentioning
confidence: 99%
“…Most foreseeable adverse reactions result from decreased pro-inflammatory genes and increased expression of anti-inflammatory and regulatory proteins [24]. Research into individual genetic factors is also needed to elucidate the patient-specific PK and PD profile, enabling customisation of glucocorticoid therapy and therefore improved patient outcomes [25][26][27][28][29][30][31][32]. This study has aimed to investigate the role of high dose intravenous mPSL pulse therapy in paediatric patients with neurological complications diagnosed with HUS and to determine whether steroids may be of clinical benefits for treating CNS complications during the acute phase of the disease.…”
Section: Introductionmentioning
confidence: 99%